Diversity of weed flora in different stages of oil palm plantation - Husnatulyusra, binti Shari (Faculty of Resource Science and Technology, 2012)
Weeds are the unwanted plants that grow aggressively, restrict sunlight and compete with desirable plants for nutrients. The weeds composition in the one year - old, three year - old, five year - old and 12 year old oil palm plantations in Maju Gemilang Oil Palm Plantation Gedong, Kota Samarahan, Sarawak was investigated to determine the diversity of weed flora, the dominant species, biomass estimation and carbon stocks of weeds. Sampling was carried out using square quadrate measuring 1 m x 1 m. All weeds were identified, counted, recorded and dried for dry weight determination. The samples were oven dry at 60 °C for 7 days. Shannon - Weiner Diversity Index obtained were 1.63,0.19,0.88, and 2.93 in one year - old, three year old, five year - old and 12 year old of oil palm plantations respectively. Nephrolepis biserrata (Sw.) Schott was the most dominant species - one year - old (SDR 45.06), three year - old (SDR 79.51) and five year - old (SDR = 54.13). Twelve year - old plantation was dominated by Asystasia intrusa (Forssk.) with SDR 17.61. The estimated carbon stock was 0.22 tonne/ha for one year - old plantation, 0.57 tonnelha for three year - old plantation, 0.45 tonne/ha for five year - old plantation and 6.37 tonne/ha for 12 year - old plantation.